THE DYNAMICS OF GENDERED PERCEPTIONS TOWARD GPT USE BY UNIVERSITY LECTURERS IN ENGLISH ACADEMIC WRITING - Rina Wahyuni; Weda Ayu Ardini (Premise: Journal of English Education and Applied Linguistics, 2026)
Artificial Intelligence (AI) has increasingly transformed higher education, particularly in the domain of academic writing. Among AI tools, Generative Pre-trained Transformer (GPT) has been widely adopted to support drafting, editing, and enhancing scholarly texts. However, limited attention has been given to how gender influences lecturers’ perceptions of GPT, especially in Indonesia where publishing in English remains both a professional requirement and a challenge. This study investigates gendered perceptions of GPT adoption in academic writing. A descriptive qualitative design was employed, involving 10 lecturers (5 male and 5 female) selected from a larger pool of 40 participants across disciplines. Semi-structured interviews were conducted and analyzed thematically using NVivo 12 within the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Findings reveal distinct gender-based differences: male lecturers emphasized efficiency and speed, while female lecturers expressed concerns regarding quality, ethics, and accuracy. Moderator variables such as age, technological experience, and voluntariness of use further shaped these perceptions. The study concludes that gender functions as a significant contextual moderator in GPT adoption in academic writing. These insights contribute to refining technology acceptance models and highlight the need for inclusive training programs in higher education that address gender dynamics and promote equitable use of AI tools.